Justiça de Transição no Brasil: análise da decisão do STF, na ADPF 153, e da Corte Interamericana de Direitos Humanos, no caso Gomes Lund e outros (“Guerrilha do Araguaia”) vs. Brasil e o princípio da prevalência dos direitos humanos - Henriques, Tharuelssy Resende (2020)
Analyzing transitional justice is an important way of verifying the stage of (re) democratization in a country. In Brazil, analyzing transitional justice in its entirety requires a study of how the Amnesty Law has been interpreted and applied. In this context, the Brazilian Amnesty Law was discussed on two important occasions, the first internally, within the scope of ADPF 153, judged by the STF, and the second at the international level, within the case of the Gomes Lund Case and others (“Guerrilha do Araguaia”) vs. Brazil, tried by the Inter-American Court of Human Rights (CtIDH). In this sense, the research problem of this work aimed to verify how the main elements of argumentation and decision used in these judgments were constructed, in order to present possible hypotheses of advantages / disadvantages for transitional justice and human rights, under the victims' perspective. Thus, the general objective was to analyze the two decisions comparatively, and in a specific way: to present theoretical assumptions about transitional justice; contextualize, describe and analyze the preferred arguments in these two decisions; comparatively analyze the two judged; present some developments after the two judged. In the end, through the analysis of these two judicial decisions, the dissertation / research postulate was reached, pointing out hypotheses of how the decision (s) enabled different ways of executing / realizing the human rights of victims of the military regime and possibilities for transitional justice. The methodology used to carry out the research, which has a descriptive character, relied on the method of inductive approach with comparative procedure and technique of direct and indirect documentation and with the methodological support of the theories and tools for analyzing the judicial decision and qualitative analysis of the results.